Changing patient and stone features for shock wave lithotripsy (SWL) in Turkey - (:unkn) unknown (Kluwer Academic Publishers, 1995)
Shock wave lithotripsy (SWL) has made a revolution in the treatment of urolithiasis. Recent reports suggesting that stone features for SWL have changed during the last years have forced us to compare our initial and last 250 patients treated at our ESWL unit in terms of stone and patient characteristics. We found that the number of ureteric stones and small calyceal stones have increased significantly with time whereas the number of larger stones undergoing SWL has decreased significantly. We believe that this change in stone features is caused by the changing trends in the treatment of stone disease by incorporating other therapeutic options and modifying the SWL indications according to patient characteristics. We also believe that prophylactic lithotripsy for asymptomatic calyceal stones still remains to be a debatable issue. © 1995 Akadémiai Kiadó.